(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
GSR (Gunshot Residue) also known as gun powder highly found as evidence on the crime scene. Combination of unburnt and partially burnt propellant powder as well as particles from the ammunition, primer, smoke, grease, lubricants and metal from the cartridge. The detection process of GSR and the test performed are very lengthy and time taking due to which investigation gets slower and cases are pending. Use of nanoparticles for the detection of GSR can make the process quick and easy in primary survey.